Limestone Microfacies of Baturaja Formation along Air Rambangnia Traverse, South OKU, South Sumatra - Sigit Maryanto (Indonesian Journal on Geoscience, 2014)
DOI: 10.17014/ijog.v1i1.173Limestones of the Baturaja Formation occur at Air Rambangnia traverse, South Ogan Komering Ulu, South Sumatra, and they are used as objects for microfacies studies. The microfacies studies are based on a detailed petrographic analysis of thirty four limestone samples, taken from the traverse. Four types of the limestones are identified such as wackestone, packstone, grainstone, and floatstone. At least five microfacies form the limestone succesion of the Baturaja Formation. They are interpreted as sedimentary facies of very restricted bay and pond, back reef local slope, slope and shelf edge, winnowed platform edge sand, and reef flank facies.